Stochastic dependency in life-cycle cost analysis of multi-component structures. Issue 5 (4th May 2019) - Saad, Lara; Chateauneuf, Alaa; Raphael, Wassim
Abstract: It is crucial to assure that civil engineering structures can operate properly and safely, as damages during the service life may lead to catastrophic loss of property, fatalities and long-term consequences. The approaches for structural management through a life-cycle cost analysis need to address explicitly the dependencies between elements. The evaluation of the life-cycle maintenance cost of structures in this article considers stochastic, degradation and economic dependencies. A new approach to include stochastic and degradation dependencies, structural redundancy and load redistribution in structural management is developed herein. The proposed model uses the fault tree analysis and the conditional probabilities to take into account stochastic dependencies between the structural elements. The degradation consequences are evaluated and a method is proposed to account for load redistribution. Also, a practical formulation to approximate the reliability of systems formed by interrelated components is proposed, by the mean of a redundancy factor that can be computed by structural analysis. The proposed approach provides effective optimal maintenance decisions for civil engineering structures by considering the interaction between elements.